FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN BUKU KIA TERHADAP IBU HAMIL - Umi Kalsum; Febriyeni Febriyeni (Maternal Child Health Care, 2020)
KIA Book is a tool to detect early the presence of maternal and child health problems or problems. An initial survey conducted in the work area of the Tigo Baleh health center in Bukittinggi, researchers asked several questions regarding the use of MCH books on 10 pregnant women. 4 pregnant women utilize and 6 pregnant women only save, the KIA book is used only when they want to do a checkup at the midwife's home. This study aims  to determine the factors associated with the use of MCH books in the work area of Tigo Baleh Health Center in Bukittinggi City in 2018. Population of all pregnant women in 2018, a sample of an average monthly visit at the Tigo Baleh health center in Bukittinggi city in 2018 was 60 people, purposive sampling technique was taken. Implemented in the work area of Tigo Baleh Health Center, Bukittinggi City. Data  analysis in this research uses univariate and bivariate. The results of this study showed that 31 respondents (52%) had  a  large number of respondents with poor knowledge, 35 respondents (58%) had a low motivation level, 33 respondents (55%) had the most role as health workers, most of them Primigravida parity respondents were 43 respondents (72%), most respondents did not use 27 KIA books (45%). There is a meaningful relationship to knowledge, motivation, the role of health workers and parity in the use of MCH books The conclusion in this study there is a relationship between knowledge, motivation, the role of health workers and parity on the use of MCH books on pregnant women in the work area of Tigo Baleh Health Center in Bukittinggi City in 2018. understand, bring the KIA Book so that the mother knows very much the benefits that exist in the KIA Book from pregnancy to 5 years old child. Keywords : Knowledge, Motivation, Role of Health Workers, Parity, KIA Book Use